Habitats - Agarwal, Tanya Luther (New Delhi The Energy Resources Institute, 2011)
Learn about the strangest and oddest natural animal homes on earth$1 (Bwalnut-sized hummingbird nests, underground badger setts with interlinked tunnels, icy polar bear dens, fire ant mounts that can house thousands of ants$1! =(Band many more.s
Keywords: Habitats; House